Sharing Session Literasi Keuangan: Pentingnya Perencanaan Keuangan dengan Bijak di Era Modern - Imtiyaz Farras Mufidah (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
Financial planning amidst the uncertainty and increasingly complex challenges of life. Every individual is required to have the ability to manage their finances wisely. In the modern era, online shopping and transactions are increasingly easy, resulting in wasteful lifestyles and addictions to spending money on unnecessary expenses. The ease of online loans is hoped to provide a way out of financial problems. The increasing prevalence of online loans has led to a high default rate. A myth has emerged in society that only high-income individuals are competent in managing their money. This indicates low financial literacy, stemming from inadequate financial management practices. This research aims to discuss financial literacy regarding prioritizing needs, understanding spending habits, and how to manage salary allocation wisely. This community service activity was conducted using a webinar method packaged as a sharing session via Zoom Meeting. This sharing session was open to the public and young people including students, employees, and housewives, totaling approximately 30 participants. It is hoped that after participating in this sharing session, participants will be able to manage their finances better and achieve their desired financial goals. Thus, it is necessary to provide information regarding education on managing finances wisely so that they can take advantage of opportunities optimally without getting caught up in financial problems.